Population pharmacokinetics of imipenem in different populations for individualized dosing: a systematic review - Zhang, Ping; Zhao, Yuhua; Zhu, Jianping; Yang, Yi; Liang, Gang; Wang, Xia; Yu, Zhenwei (Frontiers in Pharmacology, 2026)
BackgroundImipenem is a broad-spectrum carbapenem antibiotic for severe infections with significant pharmacokinetic (PK) variability. This review systematically synthesized published population pharmacokinetic (popPK) studies to identify key covariates and guide individualized dosing for patients with various conditions.MethodsA systematic PubMed and Web of Science search identified imipenem popPK models. Studies employing nonlinear mixed-effects modeling in patients with various conditions were included, and data were extracted independently by two reviewers via a standardized form. The study characteristics and PK parameter estimates were compared.ResultsThis systematic review of 18 popPK studies revealed that imipenem PKs were predominantly characterized by two-compartment models. The clearance of imipenem varied from 4.79 to 16.2 L/h in adults. Creatinine clearance (CLcr) was the most consistent and significant covariate for imipenem clearance, whereas body weight (BW) was frequently identified for volume of distribution. Other clinically relevant covariates, including the glomerular filtration rate (GFR), age, and serum ALB level, were also incorporated into the final models for specific patient subpopulations. All models applied internal validations, such as bootstrap and visual predicative check, but only three studies performed external validation.ConclusionThis review systematically integrates existing popPK models of imipenem, highlighting renal function and BW as key covariates. This study provides valuable insights for individualized dosing while identifying critical research gaps, particularly the need for external validation and focused studies in special populations.